Axially functionally graded design methods for beams and their superior characteristics in passive thermal buckling suppressions. (1st February 2021) - Li, Zhenyu; Song, Zhiguang; Yuan, Wei; He, Xiao
Abstract: Thin-wall structures on high-speed spacecrafts are usually exposed to extreme thermal environments during their service life. This problem will lead to the buckling and instability of structures, which can seriously affect the integrity and reliability of spacecrafts. Therefore, it is significant to study the suppression methods for the thermal buckling. It is well known that temperature change will produce a negative stiffness, which may eventually lead to the thermal buckling of structures. Based on this mechanism of thermal buckling, it is reasonable and effective to construct the equivalent positive thermal stiffness by changing the geometrical sizes and material properties of the structure along the axial direction. Inspired from this, in this paper, two passive ways, i.e. the axially functionally graded (AFG) design and adding torsional springs, are investigated. For the AFG design, both the thickness and material properties are functions of the axial spatial variable. In order to obtain the optimal functions for the thickness and volume fraction, an incremental structural stiffness method is proposed, and the genetic algorithm (GA) is also introduced. Numerical results show that through the AFG design, the thermal buckling characteristics of the structures are improved significantly. On the other hand, when the torsional springs are added to the main structure, under appropriate stiffness coefficients, the structural stiffness reduction caused by the temperature change can be offset to the maximum extent by the passive stiffness generated by the torsional springs. The present study is significant in the structural design of aerospace vehicles.